2007
DOI: 10.1007/s10796-007-9047-2
|View full text |Cite
|
Sign up to set email alerts
|

An examination of private intermediaries’ roles in software vulnerabilities disclosure

Abstract: Software vulnerability disclosure has generated much interest and debate. Recently some private intermediaries have entered this market. This paper examines the effects of such private intermediaries on optimal timing of disclosure policy made by public intermediaries and vendors' reactions. Our analysis of private intermediaries' role suggests that public intermediary's optimal disclosure time does not change with private intermediary's participation. However, a vendor's patch time increases when the probabil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 10 publications
0
9
0
Order By: Relevance
“…Our research makes a significant contribution to our understanding of vendor's investment in software quality, in particular recent work in the information security literature that has examined vendor patch release behavior (Arora et al, forthcoming;Cavusoglu et al, 2005;Choi et al, 2005;Li and Rao, 2007). To our knowledge our research is the first to demonstrate how increases in disclosure threats from rivals and non-rivals influences investments in information security and software quality.…”
Section: Introductionmentioning
confidence: 65%
See 1 more Smart Citation
“…Our research makes a significant contribution to our understanding of vendor's investment in software quality, in particular recent work in the information security literature that has examined vendor patch release behavior (Arora et al, forthcoming;Cavusoglu et al, 2005;Choi et al, 2005;Li and Rao, 2007). To our knowledge our research is the first to demonstrate how increases in disclosure threats from rivals and non-rivals influences investments in information security and software quality.…”
Section: Introductionmentioning
confidence: 65%
“…Telang and Wattal (2007) use an event study methodology to show that vulnerability disclosure leads to a loss of market value. Li and Rao (2007) empirically examined the role of private intermediaries on the timing of patch release by vendors and found that the presence of private intermediaries decreases vendors' incentive to deliver timely patches. Our research is similar to prior work in that we examine the economic outcomes from vulnerability disclosure.…”
Section: Related Literature and Contributionmentioning
confidence: 99%
“…A vulnerability could either be disclosed immediately with full details after it is discovered, or be disclosed after a certain period of time with limited details to allow the vendors to develop and release the patch [Li and Rao 2007]. Vulnerability disclosures have conflicting effects.…”
Section: Vulnerability Disclosuresmentioning
confidence: 99%
“…They find that software vendors wait longer than is socially optimal to release a patch and threat of disclosure can force the vendors the release the patch early. See Li and Rao (2007) for a detailed discussion on vulnerability disclosure policies.…”
Section: Information Economics and Disclosure Policymentioning
confidence: 99%